Acute Toxicity Assessment of Dyeing Industry Effluent in Fish: Investigating Time-Dependent Lethal Concentrations - Sujitha, V.M. Geo; Jones, R.D. Stevens (Journal of Neonatal Surgery, 2025)
This article highlights the importance of toxicity studies in assessing the adverse effects of agents on living organisms, focusing on product safety and environmental protection. It discusses the Indian regulatory landscape, including the Central Drugs Standard Control Organization (CDSCO) and Schedule Y of the Drugs and Cosmetics Rules, as well as ethical oversight by the Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA). It also presents a materials and methods section for an acute toxicity study involving fish exposed to raw dyeing industry effluent, focusing on determining the 96-hour LC50 using Probit analysis. The results show that even initially "safe" concentrations can become lethal over prolonged periods, emphasizing the relevance of acute toxicity data for regulatory bodies and risk assessment